Racialized Youth in the Public Library: Systemic Racism Through a Critical Theory Lens - Matthews, Amber (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
Public libraries are on the frontline of serving underprivileged groups like racialized youth and help them to mitigate social inequities that manifest in negative outcomes like education gaps, underemployment and access to safe and affordable housing. Although racialized youth account for half of the youth population in Canadian cities like Toronto, their experience in public libraries is an unstudied area of Canadian LIS scholarly and professional research. Existing research approaches youth as a homogenous group in terms of age and biological stages and does not account for race, class, and urbanism. However, racialized youth face different challenges in which race and systemic racism are a facet of everyday life. This work aims to reverse racial neutrality in public libraries by demonstrating how ambivalence about race perpetuates systemic inequalities and the disengagement of racialized youth. It draws on interdisciplinary research to show how the race-blind approach is not reflective of the needs of communities being served. Using a Critical Race Theory (CRT) framework, it shows that public libraries can implement processes to gather race-specific data under the recently-implemented Anti-Racism Act (2017). This will provide a contextual understanding of the racial make-up of users and provide a valuable frame of reference to support efforts to build stronger and more effective relationships.